(3GdLhGH GdbGWY ddJehjg YeG jQO Ydi GdMceI hGdJfRjgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdPi CWdYfG Ydi eYQaI CSQGQ JfRjdg , hhabfG deG CdgefG ef JMbjb eYGfjg GddWQjag hCMcGe JChjdg s
(3BNQgG (B:s
(3adjWGdYg ai cJGHfG GdedbH HGdTGed , aEfg jLO ajg eG jcai hjTai , hGdMeO ddg QH GdYGdejf Je GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJYdjbGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B10) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs